The Removal of Uranium and Thorium from Aqueous Solutions Onto by-pass Cement Dust (BCD) - M. Ali Omnia; H. H. El-Kashif; S. A. Sayed; M. E.H. Shalabi (Eurasian Chemico-Technological Journal, 2009)
The adsorption behavior of uranium and thorium from aqueous solutions by By-pass cement dust (BCD) has been investigated by a batch technique. The uranium and thorium adsorption on BCD was studied as a function of initial concentration, weight of BCD, pH, shaking time and temperature. The uptake of uranium and thorium at the determined optimum conditions follows Freundlich isotherm. The adsorption control of both thorium and uranium are first order and uptake energy of activation Ea =10 and 15 kJ/mol for thorium and uranium respectively. Thermodynamic parameters such as О”Ho, О”So and О”Go were also investigated.